Agenda Setting in the Establishment and Management of Green Kayen as a Tourism Destination in Condongcatur Village - Ndou Baru, Dominggus; Sumarto, Rumsari Hadi (GOVERNABILITAS (Jurnal Ilmu Pemerintahan Semesta), 2025)
This research examines the agenda setting for the establishment and management of Green Kayen as a tourist destination in Condongcatur sub-district, Kapanewon Depok, Sleman, Yogyakarta Special Region. The research focuses on the situation of Green Kayen tourism by identifying the main issues such as environmental problems, infrastructure needs and tourism economic potential, as well as looking at the involvement of various stakeholders in the formation and management of Green Kayen tourism. This research uses qualitative methods with data collection techniques through observation, interviews and documentation. Data analysis techniques used data reduction, data presentation, data validation, and conclusion drawing. The results showed that the dynamics of relationships between actors, especially between the Kalurahan Government, Pokdarwis, and Bumkal, and the community significantly influenced the agenda setting process. The Village Government is more dominant in strategic policy-making, while Pokdarwis is less involved in the process, so it is necessary to strengthen collaboration between actors and more inclusive management to support the sustainability of Green Kayen as a tourist destination in Condongcatur Village.